Exploring the selectivity and engineering potential of an NRPS condensation domain involved in the biosynthesis of the thermophilic siderophore fuscachelin - Ho, Y. T. Candace; Izoré, Thierry; Kaczmarski, Joe A.; Marschall, Edward; Ratnayake, Minuri S.; Tailhades, Julien; Steer, David L.; Schittenhelm, Ralf B.; Tosin, Manuela; Jackson, Colin J.; Cryle, Max J. (Frontiers in Catalysis, 2023)
In nonribosomal peptide synthesis, condensation (C) domains are key catalytic domains that most commonly link carrier protein bound substrates to form peptides or depsipeptides. While adenylation domains have been well characterized due to their role in the selection of monomers and hence as gate keepers in nonribosomal peptide biosynthesis, C-domains have been the subject of debate as they do not have apparent “A-domain like” side chain selectivity for their acceptor substrates. To probe the selectivity and specificity of C-domains, here we report our biochemical and structural characterization of the C3-domain from the biosynthesis of the siderophore fusachelin. Our results show that this C-domain is not broadly flexible for monomers bearing significantly alternated side chains or backbones, which suggests there can be a need to consider C-domain specificity for acceptor substrates when undertaking NRPS engineering.